A randomized controlled trial of three‐dimensional versus two‐dimensional imaging system on duration of surgery and mental workload for laparoscopic gastropexies in dogs. Issue 5 (17th April 2021) - Balsa, Ingrid M.; Giuffrida, Michelle A.; Mayhew, Philipp D.
Abstract: Objective: To evaluate the effect of three‐dimensional (3D) laparoscopy compared to two‐dimensional (2D) laparoscopy when evaluating duration of surgery for canine intracorporeally sutured gastropexy. Study Design: Randomized controlled clinical trial. Animals: Thirty client‐owned dogs. Methods: Dogs were randomized into 2D or 3D groups and underwent a three‐port laparoscopic intracorporeally sutured incisional gastropexy with barbed suture. Procedures were performed by a single board‐certified surgeon. Duration of surgery was recorded and workload was assessed immediately after surgery using the NASA Task Load Index (TLX). Results: Median duration of surgery was 3 min shorter for 3D versus 2D (95%CI −10 to 13; p = .51). Surgical component durations, total and component TLX scores, and intraoperative complications also did not differ between groups. In a subgroup analysis excluding the first eight cases due to presumption of a learning curve with suturing technique, total TLX score ( p = .004) and all component scores were lower for 3D as compared to 2D laparoscopy, although duration of surgery did not differ ( p = .20). Conclusion: The use of 3D laparoscopy was not associated with shorter duration of surgery when compared to 2D laparoscopy. Clinical Significance: 3D laparoscopy requires further investigation in veterinary medicine to determine its utility in decreasing surgical duration, surgical complications or surgeon mental or physical workload.